2024
DOI: 10.1038/s41598-024-56083-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dissipation kinetics and half-lives of fipronil and thiamethoxam in soil under various conditions using experimental modeling design by Minitab software

Ahmed F. El-Aswad,
Abdallah E. Mohamed,
Mohamed R. Fouad

Abstract: To determine the extent of pesticide buildup and their environmental contamination, the environmental half-lives of pesticides are examined. The influence of the factors affecting the half-lives of fipronil and thiamethoxam including soil type, sterilization, temperature, and time and their interactions was studied using experimental modeling design by Minitab software. Based on the dissipation kinetics data, fipronil concentrations reduced gradually over 60 days while thiamethoxam concentrations decreased str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, they did not conduct research in plants. In another study, El-Aswad et al (2024) [79] reported that the half-life of thiamethoxam in silty-loam soil was 15.0 days, in sandy-loam soil 20.1 days, and in loam soil 27.2 days. Thiamethoxam decomposed faster in silty and sandy soil.…”
Section: Behavior Of Thiamethoxam and Clothianidin In Young Oilseed R...mentioning
confidence: 98%
“…However, they did not conduct research in plants. In another study, El-Aswad et al (2024) [79] reported that the half-life of thiamethoxam in silty-loam soil was 15.0 days, in sandy-loam soil 20.1 days, and in loam soil 27.2 days. Thiamethoxam decomposed faster in silty and sandy soil.…”
Section: Behavior Of Thiamethoxam and Clothianidin In Young Oilseed R...mentioning
confidence: 98%